The use of IT as a tool for collection development process: a study in Perpustakaan Raja Tun Uda (RATU), Shah Alam / Mohd Khairol Hafiz Sanawi - Sanawi, Mohd Khairol Hafiz (Faculty of Information Management, 2008)
The rapid and continuing evolution of information technology has occasioned large stocks of electronic resources in libraries and created pressure for both library professionals and users to continue learning in order to provide effective service and make adequate use of the new information materials. Many activities in collection development, such as online searching of other libraries' catalog have become possible only in the last few years with the expansion of the internet. This research is mainly to find to what extent does a public library such as Perpustakaan Raja Tun Uda (RATU), Shah Alam are utilizing IT for the purpose of collection development process. This study will emphasis on the types of IT services used by the library, the system requirements for collection development, the IT skills needed for collection development and also the advantages and disadvantages of IT to Perpustakaan Raja Tun Uda (RATU), Shah Alam. The objectives of the study are to identify the types of IT services used in the collection development process, to recognize the system requirement for collection development, to identify the IT skills needed for collection development, to discover the advantages of using IT for collection development, and to recognize of the drawback of IT as a tool for collection development. This research is important for the reason that it can provide information to the librarian and staffs at the acquisition department especially those doing the selection for the materials to be purchase. The finding is also valuable for the library to know what are the basic requirements needed to adopt IT in the process of collection development, such as the training program for the staff to acquire the necessary skills to utilize the IT services. Beside that, the library will be aware of the potential and drawbacks of using IT.